Risk assessment and prediction of Ixodes ricinus tick questing activity and human tick-borne encephalitis infection in space and time in the Czech Republic - Daniel, Milan; Zitek, Kamil; Danielová, Vlasta; Kříž, Bohumír; Valter, Jarostav; Kott, Ivan (International journal of medical microbiology, 2006)
Present risk assessment and prediction of future risk of humans exposed to Ixodes (I.) ricinus tick attacks and, consequently, to tick-borne encephalitis (TBE) virus infection as one of the basic preconditions for successful TBE prevention has been intensively studied in the Czech Republic. An atlas of TBE in the Czech Republic containing predictive maps of I. ricinus high-incidence habitats and TBE risk sites identified by satellite data (Landsat 5 TM with spatial resolution 30 m) at a scale of 1:200,000 over a territory of 52,000 km(2) and maps of human TBE case distribution (1971-2000) has been prepared using remote sensing and geographical information systems technologies. The influence of climate changes on a forest ecosystem inhabited by I. ricinus has been studied in the southern region of the Czech Republic. The analysis of long-term series (1931-2000) of climatologic and phenological characteristics has been carried out. The results are compared with the long-term series of TBE incidence. The influence of weather condition on day-to-day changes of I. ricinus host-seeking activities was studied in 2001-2004. Field observations were realized in the south-eastern periphery of Prague where the experimental plots for tick monitoring were established in a relevant type of forest growth (Querceto-carpinetum). I. ricinus activities were investigated by the flagging method on three plots (200 m(2) each) in weekly intervals (March to November) during 2001-2004. The instruments for micrometeorological observations were installed between the experimental plots. Macrometeorological data were used from the nearby Czech Hydrometeorological Institute first class meteorological observatory. Simple and multiple linear regression and quadratic regression were used to test the relation between weather modification and I. ricinus host-seeking activity. Two preliminary most suitable 'models' are demonstrated.
Keywords: Host-Parasite Interactions; hodnocení rizik; roční období; Meteorological Concepts; zvířata; geografické informační systémy; Behavior, Animal; Seasons; Animals; lidé; Encephalitis, Tick-Borne; interakce hostitele a parazita; klíště; Risk Assessment; Ixodes; financování organizované; Humans; chování zvířat; Financing, Organized; meteorologické pojmy; Geographic Information Systems; klíšťová encefalitida